2015
DOI: 10.1111/mmi.12973
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the role of SNM1 in the DNA repair system of Trypanosoma brucei

Abstract: SummaryAll living cells are subject to agents that promote DNA damage. A particularly lethal lesion are interstrand cross-links (ICL), a property exploited by several anticancer chemotherapies. In yeast and humans, an enzyme that plays a key role in repairing such damage are the PSO2/SNM1 nucleases. Here, we report that Trypanosoma brucei, the causative agent of African trypanosomiasis, possesses a bona fide member of this family (called TbSNM1) with expression of the parasite enzyme able to suppress the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…The resultant data was plotted as dose response curves from which EC 50 values were extrapolated (Fig 3). Previous work has shown that TbSNM1 plays an important role in resolving the damage caused by mechlorethamine with our data confirming this earlier finding [42]: Cells lacking TbSNM1 are >8-fold more susceptible to this compound as compared to controls. A similar alteration in sensitivity was also observed in cells deficient in TbMRE11, TbCSB or TbEXO1 although the difference in EC 50 values displayed by these 3 mutants relative to wild type was not as great as that noted for Tb snm1 Δ cells; Tb mre11 Δ, Tb csb Δ and Tb exo1 Δ cells were 3-, 4- and 2-fold more susceptible to mechlorethamine than wild type, respectively (Figs 3A-C) This could suggest the relative importance of each enzyme in T. brucei ’s so-called ICL REPAIRtoire.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The resultant data was plotted as dose response curves from which EC 50 values were extrapolated (Fig 3). Previous work has shown that TbSNM1 plays an important role in resolving the damage caused by mechlorethamine with our data confirming this earlier finding [42]: Cells lacking TbSNM1 are >8-fold more susceptible to this compound as compared to controls. A similar alteration in sensitivity was also observed in cells deficient in TbMRE11, TbCSB or TbEXO1 although the difference in EC 50 values displayed by these 3 mutants relative to wild type was not as great as that noted for Tb snm1 Δ cells; Tb mre11 Δ, Tb csb Δ and Tb exo1 Δ cells were 3-, 4- and 2-fold more susceptible to mechlorethamine than wild type, respectively (Figs 3A-C) This could suggest the relative importance of each enzyme in T. brucei ’s so-called ICL REPAIRtoire.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, TbRAD5 and TbREV3 although not primarily involved in resolving ICLs, were also taken forward to determine whether their activities in this repair network becomes apparent in the absence of TbSNM1: The role of some yeast factors in ICL repair are only apparent when the activity of another DNA repair protein is missing [63]. To generate the double null mutant lines, the hyg-and neo -based integration vectors for each targeted gene were linearised and sequentially transformed into T. brucei Tb snm1 Δ cells (in this mutant line, Tbsnm1 has been disrupted using vectors based around resistance cassettes that includes the gene encoding for blasticidin-S-deaminase (bla) or puromycin N-acetyltransferase ( pac ) [42]). Following selection, all putative double null clones were validated using the PCR-based strategies outlined previously with this confirming that the introduced DNA fragments had integrated into the T. brucei genome and that the recombinant parasites were no longer expressing both disrupted genes (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations